A Qualitative Study About Reliefs Meaning Of Plaosan Temple: The Buddhist Tourism Destination At Klaten, Central Java - Arina Afiyati Shadikah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
This study belongs to qualitative research. This recent study focuses on the history of Plaosan temple and the reliefs meaning existed at Plaosan Temple located at Klaten Regency, Central Java. The subject of this study was the Plaosan temple itself. This study aims to identify reliefs meaning of Plaosan temple and also the history of it. The method of this study is qualitative. The data were collected using observation, interview, and documentations. The data collected were analyzed qualitatively. The history of Plaosan temple was taken from the interview with an archeologies at Central Java Institute for Preservation of Cultural Heritage and documentation from some sources founded at the library of this institute. The reliefs meaning was taken from the interview. However, the observation was done for the preliminary study. The research finding showed that there were there were three types of reliefs of Plaosan temple. Those were shaped characters, ornamental decoration, and animals. Each relief character had their own meaning. Character involved the character of a man and a woman which symbolized gender equality existed in the past, ornamental decoration about plants and tendrils showed about human’s life, and animal reliefs that consist mythological animals of Kara and Makara symbolized about reminder and teachings for human being.